(untitled) (Bangladesh Journal of Medical Science, 2012)
Primary squamous cell carcinoma of the kidney is a rare clinical entity. Primary squamous cell carcinoma is more frequently reported in urinary bladder and male urethra than in kidney. Primary renal squamous cell carcinoma (RSCC) accounts for less than 5% of urothelial tumours in urinary system. Very few cases of primary squamous cell carcinoma of kidney have been reported in the world literature. Only forty-six cases over forty four years had been reported from Mayo Clinic. These neoplasms are highly aggressive and locally advanced or metastatic at the time of presentation. Here we report such a case of primary squamous cell carcinoma of kidney in a 50-year-old lady at a locally recurrent stage with fistulous tract formation. Palliative radiotherapy came out to be a good clinical modality even in locally recurrent stage in this patient. DOI: http://dx.doi.org/10.3329/bjms.v11i3.11734 Bangladesh Journal of Medical Science Vol. 11 No. 03 July12